Pengembangan Media Pembelajaran SICABOX Materi Sifat-sifat Cahaya untuk Meningkatkan Kemampuan Berpikir Ilmiah Siswa - Syaipul, Ahmad; Yusuf, Raudhatun Nisa; Munte, Sartika Sari; Hrp, Widiya Anggraeny A. (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Scientific thinking involves a process of combining induction and deduction. Induction involves drawing specific statements to make general conclusions, while deduction involves drawing general statements to make specific conclusions. The research method used in this study is the research and development method, also known as development research. According to Sukmadinata, research and development is a research approach to produce a new product or improve existing products. With tools like SICABOX media, students can better understand the properties of light. SICABOX media can also improve the effectiveness and efficiency of learning. The presence of SICABOX media makes students more enthusiastic and eager to learn.